EFFECTIVENESS OF PROBLEM-BASED MODEL LEARNING ON LEARNING OUTCOMES AND STUDENT LEARNING MOTIVATION IN BASIC ELECTRONIC SUBJECTS - AGUS RAHMAD TIMOR; AMBIYAR AMBIYAR; OSKAH DAKHI; UNUNG VERAWADINA; MARIA MAGDALENA ZAGOTO (CV KULTURA DIGITAL MEDIA, 2021)
The purpose of this study is to find out: (1). The influence of the Problem-based learning model on student learning outcomes and motivation; (2). Students' response to learning with Problem based learning model to learning outcomes and learning motivation. This research is a pseudo-experiment. The research population is a student of Electromedical Poltekes Siteba Padang Semester IV who studied basic electronics. The study sampled 29 people, Test instruments to collect data on learning outcomes, and questionnaires for student motivation and response data. In this study, the authors conducted quantitative research using pre-experimental design method type one group pretest-posttest. The results showed that (1). There is a significant influence of the Problem-based learning model on student learning outcomes. The t-test analysis results obtained t-count of 6.9492 and t-table of 1.671 for DK of 28 with a significant level of 5%. Based on the test criteria obtained t-> t-table, this means H0. The motivation of students who use the Problem-based learning model is said to be high, judging by the average student learning motivation of 131.83; and (2). Student response from applying the Problem-based learning model is positive, judging from the average student response questionnaire score of 78.07.